(untitled) (ModaPalavra e-periódico, 2017)
Currently, if checks the evolution in women’s clothing design aiming at the well-being, comfort and quality oflife. However, women still complain of discomfort of breast movement during physical activities carried out in factory floors and sporting activities, among other activities. This discomfort, according to the women, increases during the menstrual period. Therefore, to structure the information on the subject is important, because it will suit the functional clothing designs for these activities. The mind map is a tool suitable for this because assists the organization process of thought and understanding of the information about a particular subject. With that, this work aims to structure information for project requirements with a focus on functional female clothing. The method of research is descriptive and exploratory character. In the end, this work presented project guidelines of functional guidelines female clothing through the process of analysis the mind map.